EVALUATION OF INTERNAL QUALITY CONTROL OF BIOCHEMICAL TESTS USING SIX SIGMA METRICS AT THE INSTITUTE OF TRADITIONAL MEDICINE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the current performance of internal quality control (IQC) in 2025 for 16 routine biochemical assays at different concentration levels using the Six Sigma metric, and calculating the Quality Goal Index (QGI) for tests below 4 Sigma as a basis for selecting quality control rules and implementing laboratory quality improvement.Subjects and methods: A cross-sectional descriptive study was conducted on 16 routine biochemical tests performed on the Beckman Coulter AU480 system. The Six Sigma metrics were calculated based on the total allowable error (TEa) according to CLIA 2025, using 6816 internal quality control (IQC) results collected from June to December 2025 and 352 external quality assessment (EQA) results collected from January to November 2025. The QGI was calculated based on bias (%) and imprecision (CV%).Result: 14 of the 16 analytes (87.5%) demonstrated Six Sigma performance at a good level or higher, including five analytes achieving ≥ 6  Sigma, 4 achieving 5 Sigma, and 5 achieving 4 Sigma; 2 analytes met the minimum acceptable performance level (3 Sigma). Stratified by concentration levels, nine analytes at high concentrations and six analytes at normal concentrations achieved ≥ 6 Sigma. The two analytes with 3 Sigma performance were glucose and creatinine at normal concentration levels. The QGI values were 0.95 for glucose and 0.78 for creatinine.Conclusion: This study demonstrates that the combined application of the Six Sigma scale stratified by concentration levels and the QGI enables a comprehensive assessment of the analytical performance of biochemical tests. This approach facilitates the selection of appropriate quality control rules and internal quality control frequencies for individual analytes. The findings provide a scientific basis for laboratory quality management and continuous quality improvement.
Keywords: Six Sigma, internal quality control, clinical biochemistry, laboratory quality management.